Learning Path Learn to Build a Website - Roumeliotis, Rachel (O'Reilly Media, Incorporated, 2015)
You want to create modern websites that stand out and offer all the functionality that users have come to expect. Good news-it's never been easier, even for absolute beginners. Using tools like SquareSpace, WordPress, and HTML and CSS, you can build impressive sites that no one would guess were the work of a newbie. This Learning Path gives you all the skills you need the build the sites you envision.
Online resource; Title from title screen (viewed October 15, 2015)
Keywords: Internet videos; Streaming video; Vidéos sur Internet; Vidéo en continu; streaming video; Electronic videos